BUFFALO DEVELOPMENT IN ACEH PROVINCE - Samadi, - (Proceeding Buffalo International Conference, 2013)
One of the Indonesian Government programs in animal husbandry sector is to success self-sufficient meat in 2014. In this program, buffalo meat includes the meat target besides cattle as the main meat target. Aceh is one of the provinces in Indonesia which has big number of buffalo besides other 12 provinces in Indonesia. Based on the statistical data buffalo population in Aceh Province during the last five years reduced about 41 % from 280.662 (2008) to 164.295 (2012). Reduced buffalo population in Aceh province was probably caused by bad management system and low slaughter controlling from the government. In addition, increase of meat consumption resulted in increasing buffalo slaughter each year. In Aceh, buffalo was not raised by all regions. Only specific region were raised the buffalo such as Simelue, West Aceh, Gayo Lues and Great Aceh regions. Recently Aceh government create program to improve buffalo population in Aceh with good management system. One of the programs is to purify Aceh buffalo located in Simelue island. After Aceh cattle has been approved to be one of the cattle breeds in Indonesia, Simelue buffalo has been proposed by Aceh government to be one of the buffalo breeds in Indonesia. The purpose of this review was to inform about development of buffalo in Aceh province based on secondary data.